Collatio bonorum - Kačer, Blanka (Array, 2019)
Collatio bonorum is a legal institute of inheritance law, the purpose of which is to balance the legal position of legal heirs of the same hereditary order. The balance is achieved by calculating all gifts received during the life of the testator, which means that the first thing to do is attempt to balance the position of those heirs who either have not received gifts or who have not received them to a certain extent with the position of other gift recipients – legitimate heirs of the testator, by distributing from what the testator left behind. The matter at hand is the substitution of the testator’s will sui generis. The legislator specifically stipulates which gifts are not included as well as the method of the calculation. Quite specific conditions for the possible reduction of gifts are also prescribed, but under the condition that it is the only way to preserve the legitimate portion of the heir who requested it. Although it is a relatively old legal institute, research has shown, however, that it would be necessary de lege ferenda to correct certain deficiencies.